Abnormal acoustic wave velocities in basaltic and (Fe,Al)-bearing silicate glasses at high pressures - Liu, Jin; Lin, Jung-Fu (Geophysical research letters, 2014)
We have measured acoustic VP and VS velocities of (Fe,Al)‐bearing MgSiO3 silicate glasses and an Icelandic basalt glass up to 25 GPa. The velocity profiles of the (Fe,Al)‐bearing and basaltic silicate glasses display decreased VP and VS with minima at approximately 5 and 2 GPa, respectively, which could be explained by the mode softening in the aluminosilicate networks. Our results represent the first observation of such velocity softening extending into the chemically complex basaltic glass at a relatively low transition pressure, which is likely due to its degree of polymerization, while the Fe and Al substitutions reduce sound velocities in MgSiO3 glass. If the velocity softening in the basaltic and silicate glasses can be used as analogs for understanding melts in Earth's interior, these observations suggest that the melt fraction needed to account for the velocity reduction in the upper mantle low‐velocity zone may be smaller than previously thought. Key Points Sound velocities of basalt and silicate glasses are measured at high pressureBasalt and silicate glasses show acoustic anomalies at high pressuresImplications for the upper mantle low‐velocity zone are discussed